Identification and Quantification of Single and Multi‐Adulteration of Beeswax by FTIR‐ATR Spectroscopy. Issue 12 (19th November 2019) - Tanner, Norman; Lichtenberg‐Kraag, Birgit
Abstract: Marketing of adulterated beeswax foundation has recently become a major economic problem for beekeepers. Paraffin contamination leads to collapse of combs, and stearic acid has a negative influence on the development of bee brood. The quality of beeswax for beekeeping has not been standardized in EU regulations. Recently, it was shown that attenuated total reflectance Fourier‐transform infrared spectroscopy (FTIR‐ATR) can be used to determine beeswax adulteration. Differences in the IR spectra of authentic beeswax can be identified and calculated through comparison with authentic beeswax. In this study, the method is further validated by employing a high number of samples of authentic beeswax from different origins. Low quantification and detection limits are achieved for paraffin, stearic acid, tallow, carnauba wax, and candelilla wax. Furthermore, the FTIR‐ATR analytical conditions are verified by analyzing 358 samples of commercial and beekeeper‐produced beeswax foundations. Multi‐adulterated samples with as many as five different additives in beeswax mixtures are identified with the same accuracy as single substances. Additionally, the spectra of a further 14 different natural and synthetic waxes and hardened fats are analyzed and are compared with beeswax. Finally, a spectral library is established that can be used for further studies. Practical Applications : FTIR‐ATR is a fast and cost‐efficient tool in beeswax analysis for accurately monitoring a high sample volume. Analysis of 358 beeswax foundations showed an adulteration of 21.8% of the samples with paraffin, stearic acid, tallow, and combinations. Based on the results of this study, it is possible to detect beeswax adulteration of less than 3% of these adulterants and their combinations by FTIR‐ATR spectroscopy. This method can be used for monitoring beeswax foundations to identify adulterated materials, exclude these materials from the recycling process, and produce high‐quality beeswax, which is essential for bee health. Abstract : Attenuated total reflectance Fourier‐transform infrared spectroscopy is used to determine beeswax adulteration. In this study, the method is further validated by employing a high number of samples of authentic beeswax. Low quantification and detection limits are achieved for paraffin, stearic acid, tallow, carnauba wax and candelilla wax. Multi‐adulterated beeswax are identified with the same accuracy as single substances.